Empowering Vocational Learning: Animated Video and Talking Stick Methods in Hand-Foot Care - Ayudyah Khusuma Wardani; Neneng Siti Silfi Ambarwati; Efri Sandi (Journal of Pedagogi, 2025)
In hand and foot care, vocational education often faces challenges related to student engagement and skill mastery. This study aims to evaluate the effectiveness of a combined instructional approach using animated video media and the talking stick method to enhance practical learning outcomes. Employing a quasi-experimental design with a pretest-posttest approach, participants were vocational students (n = 60) specializing in beauty and wellness courses at a local training center. They were divided into two groups: an experimental group receiving animated video lessons augmented by collaborative discussions using the talking stick, and a control group receiving conventional lecture-based instruction. Data were gathered through standardized skill assessments, knowledge-based quizzes, and focus group interviews. Quantitative results showed a statistically significant improvement (p < 0.05) in both theoretical understanding and practical proficiency in the experimental group compared to the control group. Qualitative findings revealed heightened engagement and self-confidence among students participating in the interactive sessions. These outcomes suggest that integrating animated video, which provides clear, step-by-step demonstrations, with the talking stick approach, which ensures equitable participation and fosters collaboration, can substantially enrich vocational learning experiences. This study highlights the potential for innovative, interactive teaching methods to improve student outcomes in skill-based disciplines, recommending broader adoption of multimedia-supported and discussion-driven strategies in vocational curricula.